Creativity and the wandering mind : spontaneous and controlled cognition - Preiss, David D.; Cosmelli, Diego; Kaufman, James C. (Explorations in creativity research., 2020)
Creativity and the Wandering Mind summarizes research on the impact of mind wandering on creativity, including imagination, fantasy, and play. Most coverage in this area has either focused on the negative consequences of mind wandering on focused problem solving or the positive effect of mindfulness, but not on the positive consequences of mind wandering. This volume bridges that gap. Research indicates that most people experience mind wandering during a large percentage of their waking time, and that it is a baseline default mode of brain function during the awake but resting state. This volume explores the different kinds of mind wandering and its positive impact on imagination, play, problem-solving, and creative production --publisher.